A randomized, double‐blind, placebo‐controlled, phase 3 study of tivantinib in Japanese patients with MET‐high hepatocellular carcinoma. Issue 10 (26th August 2020) - Kudo, Masatoshi; Morimoto, Manabu; Moriguchi, Michihisa; Izumi, Namiki; Takayama, Tetsuji; Yoshiji, Hitoshi; Hino, Keisuke; Oikawa, Takayoshi; Chiba, Tetsuhiro; Motomura, Kenta; Kato, Junko; Yasuchika, Kentaro; et al.
Abstract: A previous randomized phase 2 study of hepatocellular carcinoma revealed that the c‐Met inhibitor tivantinib as second‐line treatment significantly prolonged progression‐free survival in a subpopulation whose tumor samples highly expressed c‐Met (MET‐high). Accordingly, this phase 3 study was conducted to evaluate the efficacy of tivantinib as a second‐line treatment for Japanese patients with MET‐high hepatocellular carcinoma. This randomized, double‐blind, placebo‐controlled study was conducted at 60 centers in Japan. Hepatocellular carcinoma patients with one prior sorafenib treatment and those with MET‐high tumor samples were eligible for inclusion. Registered patients were randomly assigned to either the tivantinib or placebo group at a 2:1 ratio and were treated with twice‐a‐day oral tivantinib (120 mg bid) or placebo until the discontinuation criteria were met. The primary endpoint was progression‐free survival while the secondary endpoints included overall survival and safety. Between January 2014 and June 2016, 386 patients provided consent, and 195 patients were randomized to the tivantinib (n = 134) or placebo (n = 61) group. Median progression‐free survival was 2.8 (95% confidence interval: 2.7‐2.9) and 2.3 (1.5‐2.8) mo in the tivantinib and placebo groups, respectively (hazard ratio = 0.74, 95% confidence interval: 0.52‐1.04, P  = .082). Median overall survival was 10.3 (95% confidence interval: 8.1‐11.6) and 8.5 (6.2‐11.4) mo in the tivantinib and placebo group, respectively (hazard ratio = 0.82, 95% confidence interval: 0.58‐1.15). The most common tivantinib‐related grade ≥3 adverse events were neutropenia (31.6%), leukocytopenia (24.8%), and anemia (12.0%). This study did not confirm the significant efficacy of tivantinib as a second‐line treatment for Japanese patients with MET‐high hepatocellular carcinoma. (NCT02029157). Abstract : Results of JET‐HCC.